Home-based work and home-based workers (1800-2021) - Nillson, Malin; Mazumdar, Indrani; Neunsinger, Silke (Studies in global social history,, 2021)
"During the Covid-19 pandemic, the home as a workplace became a widely discussed topic. However, for almost 300 million workers around the world, paid work from home was not news. Home-Based Work and Home-Based Workers (1800-2021) includes contributions from scholars, activists and artists addressing the past and present conditions of home-based work. They discuss the institutional and legal histories of regulations for these workers, their modes of organization and resistance, as well as providing new insights on contemporary home-based work in both traditional and developing sectors. Contributors are: Jane Barrett, Janine Berg, Eloisa Betti, Chris Bonner, Eileen Boris, Patricia Coñoman Carrilo, Janhavi Dave, Saniye Dedeoğlu, Laura K Ekholm, Jenna Harvey, Frida Hållander, K. Kalpana, Srabani Maitra, Indrani Mazumdar, Gabriela Mitidieri, Silke Neunsinger, Malin Nilsson, Narumol Nirathron, Åsa Norman, Leda Papastefanaki, Archana Prasad, Maria Tamboukou, Nina Trige Andersen, and Marlese von Broembsen"--